Humanistic Intention of Dystopia in "The Giver" by Lois Lowry - Muntian, A. O.; Shpak, I. V. (Anthropological Measurements of Philosophical Research, 2021)
Purpose. The aim of this piece is to study the manifestations of humanistic pursuits in a literary fiction work. The main interest is related to the interpretation of those existential and sociocultural concepts that underlie the dystopian novel by Lois Lowry. The theoretical basis of the study is based on works on phenomenology and the theory of reader reception. The method of phenomenology is a descriptive method: the phenomena of consciousness cannot be reduced to limited cognitive forms, and therefore language and means of description are important along with their ability to reveal consciousness through phenomena. Originality of the study lies in the investigation of the humanistic aspect of a dystopian society, depicted in the modern literary fiction. The main attention is focused on the phenomenological identification of existential ideas and their manifestation in the literary characters of the given work. The conclusions speak about the tendencies of humanization and dehumanization of a man and society in the context of philosophical, ethical and aesthetic issues, which are the most important and urgent problems of our time. The current study finds out that in the modern dystopian literature and philosophy, the main subject of attention is a human. This human is perceived and depicted as a phenomenon that cannot be grasped by the notions of intimation and essence. The human is a creature whose freedom presupposes a constant departure from nature and habitual reality to the realm of transcendent through the desire to comprehend his or her certain way of existence.